2013
DOI: 10.1371/journal.pone.0061594
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Antimicrobial Compounds in Plant Extracts against Multidrug-Resistant Acinetobacter baumannii

Abstract: The number of fully active antibiotic options that treat nosocomial infections due to multidrug-resistant Acinetobacter baumannii (A. baumannii) is extremely limited. Magnolia officinalis, Mahonia bealei, Rabdosia rubescens, Rosa rugosa, Rubus chingii, Scutellaria baicalensis, and Terminalia chebula plant extracts were previously shown to have growth inhibitory activity against a multidrug-resistant clinical strain of A. baumannii. In this study, the compounds responsible for their antimicrobial activity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 22 publications
(32 reference statements)
3
70
0
3
Order By: Relevance
“…The predominant feature of the inhibition curve shown by corilagin is that it is biphasic in nature. This study identified that the compound norwogonin was the highly effective compound against A. baumanii (Miyasaki et al, 2013). The 50% aqueous ethanolic extract of Acalypha wilkesiana and Acalypha hispida leaves showed good antimicrobial effect against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis and Candida pseudotropicalis (Adesina et al, 2000).…”
Section: Antibacterial Activitymentioning
confidence: 95%
“…The predominant feature of the inhibition curve shown by corilagin is that it is biphasic in nature. This study identified that the compound norwogonin was the highly effective compound against A. baumanii (Miyasaki et al, 2013). The 50% aqueous ethanolic extract of Acalypha wilkesiana and Acalypha hispida leaves showed good antimicrobial effect against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis and Candida pseudotropicalis (Adesina et al, 2000).…”
Section: Antibacterial Activitymentioning
confidence: 95%
“…41,45,46 Ellagitannins have also been reported to function via several antibiotic mechanisms including interaction with cytoplasmic oxidoreductases and by disrupting bacterial cell walls. 41,45 Interestingly, the benzopyran tannin chebulagic acid (Figure 8h) has been reported to inhibit a multi-resistant strain of Acinetobacter baumannii, 47 a species taxonomically related to A. baylyi, examined in our study.…”
Section: 20mentioning
confidence: 64%
“…The time-kill kinetic index of isolated compound was determined as described by Miyasaki et al [26] with slight modifications. The objective of this test is to know the duration of bactericidal or fungicidal effect of isolated molecule.…”
Section: Methodsmentioning
confidence: 99%